The use of intravenous valproic acid in patients with epileptic seizures developing during radiation therapy following glial tumor surgery - A. S. Shershever; D. L. Benzion; S. A. Lavrova; Y. A. Mironova; G. V. Cherkasov (Эпилепсия и пароксизмальные состояния, 2019)
Objective: to study the effect of valproic acid on epileptic seizures developing during radiation therapy (RT) following glioma surgery in patients taking antiepileptic drugs (AED).Materials and methods. This prospective observational study involved 879 patients aged 18-78 with glioblastomas (GM) who were receiving RT. The patients underwent clinical and neurological examination, electroencephalography (EEG), and neuroimaging tests. After the examination and surgical treatment, patients were prescribed RT. During an RT procedure, the patient has to stay in a steady non-moving position for 30 min. To prevent the patient from developing sporadic or serial seizures during RT, we used valproic acid administered via the intravenous route. The efficacy and safety of valproic acid were evaluated together with the outcomes of RT.Results. Of 879 participants, symptomatic epilepsy was detected in 147 patients (16.7%). An increase in epileptic seizures (even under basic AED therapy) after surgery for GM was noted on days14-21 after the start of RT (i.e. between the 7 and 11th RT session) in 65 of 147 patients (44.2%). The iv administration of valproic acid allowed all 65 patients to complete the course of RT. No adverse events associated with the use of valproic acid were reported.Conclusion. This observation from our clinical practice allows us to recommend valproic acid for the treatment of epileptic seizures (focal and generalized) developing during radiotherapy after surgery for GM. The treatment should be accompanied by clinical, neurological and EEG monitoring.